The "other" Africans : re-examining representations of sexuality in the work of Nicholas Hlobo and Zanele Muholi - Makhubu, Nomusa (Rhodes University, Faculty of Humanities, Department of Fine Art, 2008)
Nicholas Hlobo, a sculptor and performance artist, and Zanele Muholi, a photographer and activist, explore different ways of representing sexuality, particularly homosexuality. It is extremely difficult to discuss African sexuality in light of the stain of colonial attitudes that have exoticised and ascribed hypersexuality to African bodies. Moreover, sexuality is often not discussed in the construction of so-called African traditions and this has contributed to rendering African-ness as an exclusive identity. Tensions within and between categories of African-ness are compounded by constituted regulations. For example, Hlobo investigates the obligation of circumcision which seems to contrast the lifestyle and contexts in which he works and resides, and Muholi represents the existence of homosexual and transgender relations, even within conservative categories. The visual imagery of these two artists investigates the boundaries set by different social constructs. These set boundaries have also affected crimes against bisexual, transgender and homosexual individuals, which are reaching an alarming rate. Hlobo questions the validity of structures that marginalise homosexual individuals through drawing attention to the ambivalence of certain statutes. Muholi seeks to publicise the injustices imposed upon homosexual individuals in order to demonstrate the weight of that crisis. Although the South African legal system condones liberated expressions of sexual identity, due to social prejudices homosexual individuals are still treated as if they are not entitled to basic human rights. As a result, hate-crimes are not reported, and when they are they are not taken seriously. Hlobo and Muholi not only bring these issues to light, but also point out the dilemma inscribed in the social and political history of (South) Africa with regards to collective and individual identities. This thesis seeks to provide an analysis of the visual language used by Hlobo and Muholi to subvert the notion that homosexuality is "un-African" and to complicate concepts of gender, sexuality and identity.
Keywords: Hlobo, Nicholas; Muholi, Zanele; Women in art; Photography, Artistic; Homosexuality in art; Sex in art; Performance art; Art, African